(untitled) (Indian Journal of Animal Production and Management, 2013)
The study was conducted in Bhilwara district by incorporating a total 120 farmers selected from adopted and non-adopted area. Fifteen technologies in sheep husbandry practices were identified to study the adoption level among farmers - selection and purchase of quality sheep (58.33 %), provision of shelter for animals (46.67 %), feeding of colostrums to new born lamb (100 %), period of grazing (100%), feeding of crushed grain (58.33%), feeding of tree leaves in summer (70 %), deworming (73.33%), vaccination of sheep (60%) and marketing of ram lamb at 6 months of age (83.33) were adopted by majority of the participant farmers. In the case of farmers from non-adopted area, period of grazing (100%), feeding of colostrums to new born lamb (70 %) and feeding of tree leaves (50 %) were the practices adopted by farmers, while majority of them were non-adopters to the remaining practices in sheep husbandry. Majority of the adopted area expressed that the reason for non-adoption of recommended practices were lack of knowledge, lack of time and lack of veterinary services and non-availability of inputs.